2011
DOI: 10.1007/s12070-011-0412-6
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Computed Tomography in Stapedial Otosclerosis

Abstract: The value of high-resolution CT scanning in diagnosing stapedial otosclerosis and in influencing surgical planning was studied. 40 cases, consisting of patients of both genders, above the age of 14 years, with a clinical diagnosis of otosclerosis underwent HRCT of the temporal bones. Images were acquired in axial plane, with a bone algorithm, keeping slice thickness at 0.5 mm and intervals of 0.5 mm. Reconstruction of the volume data set was done to obtain overlapping slices in various planes, so as to obtain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…The authors argued that the presence of false negatives was justified by an annular fixation of the footplate. 11 This type of fixation found intraoperatively was also consistent with the histological findings of a study by Cherukapally et al 12 In 2001, Shin et al found a sensitivity of CT scans in the diagnosis of otosclerosis of 91.3%. The false negatives were also attributed to early, "infraradiological" disease.…”
Section: Overall Sensitivitysupporting
confidence: 84%
See 2 more Smart Citations
“…The authors argued that the presence of false negatives was justified by an annular fixation of the footplate. 11 This type of fixation found intraoperatively was also consistent with the histological findings of a study by Cherukapally et al 12 In 2001, Shin et al found a sensitivity of CT scans in the diagnosis of otosclerosis of 91.3%. The false negatives were also attributed to early, "infraradiological" disease.…”
Section: Overall Sensitivitysupporting
confidence: 84%
“…38 Finally, Priya et al did not find the radiological correlation between thickness of the footplate and audiometric parameters. 11 In general, location and size of otosclerotic foci seem to be poorer predictors of sensorineural HL than endosteal involvement and injuries to the cochlear integrity. 8,32…”
Section: Correlation Between Computed Tomography and Audiometric Findmentioning
confidence: 88%
See 1 more Smart Citation
“…HRCT accurately predicted thickened foot plate in 50% of cases with a sensitivity of 100% and specificity of 98% using imaging criteria of otosclerosis, which include increased thickness of foot plate >0.6 mm, grey foot plate(otospongiotic), hypodensity anterior to oval window, widened oval window and partial or complete obliteration of oval window by thickened footplate. S. R. Priya et al 9 , detected the sensitivity foot plate thickening is 85.3%. The sensitivity of detecting otosclerosis by evaluating footplate thickness may increase with thickness.…”
Section: Discussionmentioning
confidence: 95%
“…1,4 Hidden areas of the middle ear such as sinus tympani and facial recess are well appreciated in HRCT 5 , allowing better understanding of the aetiology, pathology, disease course with early detection of complications which alters treatment modality and has considerably reduced the morbidity and mortality pertaining to lesions of the temporal bone. 6 In addition to cholesteatoma, a very serious condition of the middle ear, HRCT plays a major role in the presurgical evaluation of other pathologies such as chronic suppurative otitis media (TT type), malignant otitis externa 7 , otosclerosis 8,9 and anatomical variations like high riding jugular bulb etc. The prospective study aimed to study pathologies of the temporal bone along with their complications on HRCT and to correlate with their surgical findings.…”
Section: Introductionmentioning
confidence: 99%